Investigation of the effect of using graded porosity on the thermal performance of the encapsulated ice thermal energy storage tank. Issue 1 (29th April 2019) - Erdemir, Dogan; Altuntop, Necdet
Abstract: The storage tank has great impact on the performance of ice thermal energy storage (ITES) system. Previous researches show that enhanced temperature gradient in the tank improves the thermal performance of system. This study deals with the investigation for determining the effect of using graded porosity in the storage tank of encapsulated ITES system. In this study, it was researched that the effects of uniform, two‐graded, and three‐graded porosities inside the storage tank. Energy equation in porous medium was solved analytically to determine the centerline temperature changing in the tank. At the end of study, it was found that the lower porosity supplied higher thermal performance. However, lower porosity requires higher tank volume. Graded porosity provided the almost equal thermal performance with lower uniformly distributed porosity, although it had a higher porosity. Energy efficiency values were very high and changed between 95.23% and 99.98% in all porosity structure and working conditions. On the contrary to the energy efficiency values, exergy efficiency values were changed over a wider range between 35.80% and 88.71%. The highest exergy efficiency of 88% was seen in ε = 0.4 uniform porosity. Also, ( ε 1 = 0.4, ε 2 = 0.5) two‐graded porosity and ( ε 1 = 0.4, ε 2 = 0.5, ε 3 = 0.6) three‐graded porosity provided higher exergy efficiency. While exergy efficiency increased with increasing heat transfer fluid (HTF) flow rate, decreased with decreasing HTF inlet temperature.